Evaluación del conocimiento de las madres sobre la lactancia materna y sus beneficios en el crecimiento del desarrollo cognitivo de los niños que acuden al hospital del IESS - Babahoyo 2015. - Sinmaleza Arteaga, Verónica Paola (2015)
This study was carried out to mothers who come to the hospital IESS Babahoyo, and the objective was to evaluate the knowledge of mothers about breastfeeding and its benefits in the growth of cognitive development of children, seeking to educate health mothers of the benefits of consumption of their children breast milk, especially those that present difficulties in the process of breastfeeding. In the results, it was observed that women do not know about the benefits of breastfeeding by 64% while 36% if you know your benefits. 69% of mothers are unaware of the consequences that have not provide breast milk to their children, 31% of mothers if they know the consequences for failing to provide breast milk to their babies. 80% of mothers have not received educational lectures about breastfeeding advantages and benefits, and 20% if received training on breastfeeding. The need to provide effective information from nurses for effective results in the proper use and application of breastfeeding leading to the baby benefits is established.